2021
DOI: 10.1111/ijd.15974
|View full text |Cite
|
Sign up to set email alerts
|

Association of childhood vaccination with pediatric lichen planus: A systematic review

Abstract: Lichen planus (LP) is a chronic T-cell-mediated mucocutaneous inflammatory disease, largely recognized in adults. It is uncommon in children, and the literature present still lacks comprehensive understanding mainly due to underreporting of such cases. LP shows atypical clinical features, when seen in children, mainly affecting the flexor aspect of the wrists, legs, and the oral and genital mucosae. It is largely considered an autoimmune response of the body with various etiologic factors. Its association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…At present there are no systematic reviews in the literature on OLP in children, while reviews on Lichen planus (LP) in pediatric age have been performed; Specifically, a recent systematic review has identified all cases described in the literature of lichen Planus pigmentosum which would represent 2.8% of Children with LP without referring to oral manifestations( 18 - 20 ), and other reviews have focused on the role of vaccinations for hepatitis B in association with the onset of LP in pediatric age ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present there are no systematic reviews in the literature on OLP in children, while reviews on Lichen planus (LP) in pediatric age have been performed; Specifically, a recent systematic review has identified all cases described in the literature of lichen Planus pigmentosum which would represent 2.8% of Children with LP without referring to oral manifestations( 18 - 20 ), and other reviews have focused on the role of vaccinations for hepatitis B in association with the onset of LP in pediatric age ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors emphasized that protein S provides epitopes similar to keratinocytes, which might trigger an autoimmune response driven by cytotoxic T lymphocytes [ 21 ]. Furthermore, hepatitis B and rabies vaccination were observed to be associated with pediatric LP [ 22 ]. Regarding COVID-19 vaccination, an associated onset of cutaneous LP was recently reported by Hiltun et al, Merhy et al, Piccolo et al, as well as Belina et al [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%